Analyzing the effectiveness of anti-radiation shield in reducing the effects of mobile phone emissions: article / Azizah A. Rahman - A. Rahman, Azizah
This technical paper investigates the effectiveness of anti-radiation shield in reducing mobile phone emissions using resonant field imaging system (RFI) and artificial neural network (ANN). The RFI frequency counter was used to capture the human frequency of 30 students including male and female students before and after using mobile phone with and without the anti-radiation shield. ANN was then used to further classify between samples using the mobile phone; with and without the anti-radiation shield.